(untitled) (Conference Zone, 2022)
The article discusses the effectiveness of computer systems and medical devices in the diagnosis and treatment of patients in medical institutions.The results show that it is appropriate to solve the problem of medical equipment for the diagnosis of the disease together with the problem of computerization of the patient treatment process.